2015
DOI: 10.1027/1864-1105/a000132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of News Stereotypes on the Perception of Facial Threat

Abstract: Abstract. We investigated the effects of antiforeigner political advertisements on implicit and explicit stereotypes. While stereotypical associations may become automatically activated (implicit stereotypes), individuals can reject these thoughts and decide not to use them for an overtly expressed judgment (explicit stereotypes). We hypothesized that even if citizens negated stereotypical content, advertisements might still affect implicit stereotypes. This hypothesis was tested using an experiment where part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
0
6
1
1
Order By: Relevance
“…This finding advances news stereotype-priming research by showing an effect on a highly relevant social factor (i.e., impulsive facial-threat perceptions), which has not been investigated prior to the present experiment. Although previous research revealed that media-stereotype exposure has consequences on stereotypes and attitudes, the present study indicates that media stereotypes might influence actual social behavior by influencing the impulsive perception of facial displays of stereotyped targets (see Arendt et al, 2014).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This finding advances news stereotype-priming research by showing an effect on a highly relevant social factor (i.e., impulsive facial-threat perceptions), which has not been investigated prior to the present experiment. Although previous research revealed that media-stereotype exposure has consequences on stereotypes and attitudes, the present study indicates that media stereotypes might influence actual social behavior by influencing the impulsive perception of facial displays of stereotyped targets (see Arendt et al, 2014).…”
Section: Discussioncontrasting
confidence: 80%
“…Thus, specific foreign nationalities targeted at countries (stereotypically) associated with dark-skinned inhabitants were used to prime the “dark-skinned criminal” stereotype. I used specific nations based on a pretest (Arendt et al, 2014). This pretest ensured that the reading of these specific nations (e.g., Nigeria, India, Turkey) activated the “dark-skinned” concept in the participants’ memory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not reviewed in detail above, marketing practices and media consumption can have a direct impact on perceptions and evaluations of skin tone differences. When participants read a tabloid-like news story about dark-skinned criminals, they judged subsequently presented dark-skinned faces as more threatening than light-skinned faces (Arendt, Steindl, & Vitouch, 2015). Similarly, individuals with higher levels of news viewing reported more emotional discomfort in response to a crime story about a dark-skinned Blacks perpetrator compared with less frequent news viewers (Dixon & Maddox, 2005).…”
Section: Work To Mitigate the Impact Rather Than The Expression Of mentioning
confidence: 99%
“…Third, the current study did not consider variation across outlets. Threat associations, however, might be higher in tabloid-style newspapers, who have been shown to frequently link "foreigners" with criminal behavior (Arendt, Steindl, and Vitouch 2015).…”
Section: Discussionmentioning
confidence: 98%